2019
DOI: 10.1029/2018jf004878
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Adaptation of River Channels to Vegetation Establishment: A Laboratory Study

Abstract: While the scientific community has long recognized that alluvial rivers are the product of interactions between flowing water and bed material transport, it is increasingly evident that vegetation mediates these interactions and influences the stream channel characteristics. In a novel set of mobile bed laboratory experiments with variable discharge, we demonstrate that vegetation colonization affects bank erosion rates, channel shape, channel sinuosity, and bar pattern. Our analyses compared the morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 82 publications
6
43
0
Order By: Relevance
“…The proposed approaches [7][8][9][10] to studying the processes of floodplain flow formation correspond to their natural state, rather than the artificially compressed state. The presented results of the numerical experiment allow studying the development of deformations on floodplains, in particular, in the zone of influence of a bridge crossing taking into consideration peculiarities of relief and interaction with the watercourse flow on actual objects of transport facilities.…”
Section: Discussion Of Results Of Calculation Of Deformations On Floomentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed approaches [7][8][9][10] to studying the processes of floodplain flow formation correspond to their natural state, rather than the artificially compressed state. The presented results of the numerical experiment allow studying the development of deformations on floodplains, in particular, in the zone of influence of a bridge crossing taking into consideration peculiarities of relief and interaction with the watercourse flow on actual objects of transport facilities.…”
Section: Discussion Of Results Of Calculation Of Deformations On Floomentioning
confidence: 99%
“…According to the above [7] results of laboratory research with a movable vegetation layer, deformation development rate, the formation of a floodplain flow and of the relief of floodplains themselves are caused by vegetation distribution, growth and origin. The lack of vegetation contributes to the flow formation with the smallest winding, river vegetation slows down the deformation development on floodplains and promotes watercourse deepening.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Our results are consistent with other recent evidence available in the literature. Vargas-Luna et al (2019) showed that vegetation encroaching on a sinuous sand-bedded channel in flume experiments caused the main channel to become deeper and the bars to increase in elevation because of sedimentation. Similarly, Lightbody et al (2019) Despite the limits of simplifying natural river processes in a flume experiment, it seems quite relevant that the topographical nature of a river system forced by vegetation is consistently different in terms of the vertical distribution of elevations and synthetic indexes of semivariograms, if compared with what is measured in a braided river without vegetation.…”
Section: The Morphological Role Of Vegetation In Braided Riversmentioning
confidence: 99%
“…Conversely, bank height may limit bank erosion (Bufe et al., 2019). Vegetation is known to increase the cohesion and to limit the erosion of channel banks (Vargas‐Luna et al., 2019), to slow down the lateral mobility of meanders (Lelpi & Lapotre, 2020), and to increase the minimum stress that needs to be overcome in order to detach blocks from the flanks (Langston & Temme, 2019).…”
Section: Introductionmentioning
confidence: 99%